2021
DOI: 10.25270/wmp.2021.10.4247
|View full text |Cite
|
Sign up to set email alerts
|

Healing of a Chronic Pressure Injury in a Patient Treated With Medical Cannabis for Pain and Sleep Improvement: A Case Report

Abstract: BACKGROUND: A small body of evidence suggests medical cannabis may facilitate wound healing, but the exact mechanism of this effect is unclear. PURPOSE: This case report describes a patient with a pressure injury (PI) who received cannabis oil treatment for pain management and sleep improvement. METHODS: A 37-year-old woman with multiminicore disease, scoliosis, short-chain acyl-CoA dehydrogenase deficiency, and epilepsy presented to the Neurology Centre of Toronto with chronic pain and sleep disturbance, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Diaz et al 49 published a case report where they described a patient who was treated with oral cannabis oil, which included a combination of CBD and THC, to treat a chronic pressure ulcer.…”
Section: Human Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Diaz et al 49 published a case report where they described a patient who was treated with oral cannabis oil, which included a combination of CBD and THC, to treat a chronic pressure ulcer.…”
Section: Human Studiesmentioning
confidence: 99%
“…A foam padded dressing was the only other intervention applied which may have confounded the effect of the cannabis oil treatment. 49 Maida et al 47,48 possible benefit in both studies, their study design did not include a control group making it difficult to determine if the TCBMs led to the wound closure. 47,48 In another case series, three patients self-initiated various topical formulations of CBD to treat epidermolysis bullosa (EB) lesions.…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study with 2224 patients by Maurer et al revealed that the patients’ post-injury three and four-week use of cannabis after concussions resulted in a lower severity score but not faster recovery from concussion symptoms [ 5 ]. The case report of Diaz et al on a patient with pressure injury exhibiting pain and sleep problems was given with three different medical cannabis oils (1 CBD-dominant and 2 THC-dominant) in increasing doses and revealed an improvement in sleep quality with a decrease in pain and anxiety [ 21 ]. An incidental wound improvement was noticed starting at two weeks post-treatment [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…The case report of Diaz et al on a patient with pressure injury exhibiting pain and sleep problems was given with three different medical cannabis oils (1 CBD-dominant and 2 THC-dominant) in increasing doses and revealed an improvement in sleep quality with a decrease in pain and anxiety [ 21 ]. An incidental wound improvement was noticed starting at two weeks post-treatment [ 21 ]. These studies highlighted different benefits of CBD on different areas of the body, making the potential value of the CBD product even greater.…”
Section: Reviewmentioning
confidence: 99%